PENGARUH STRUKTUR MODAL, PROFITABILITAS, UKURAN PERUSAHAAN DAN KEBIJAKAN DIVIDEN TERHADAP NILAI PERUSAHAAN - Erin Dwi Nurfebriastuti; Agus Sihono (JURNAL ILMIAH RESEARCH AND DEVELOPMENT STUDENT, 2023)
This study examines the effect of capital structure, profitability, firm size, and dividend policy on firm value. The purposive sampling method was used to take samples of secondary data on the annual reports of 13 banking companies listed on the Indonesia Stock Exchange with a research period of 2019-2022. Data were analyzed using multiple linear regression with SPSS version 25. The findings in this study indicate that capital structure and firm size have no effect on firm value, while profitability and dividend policy have a significant positive effect on firm value. This research is expected to provide information and knowledge for companies about value, and also as input for potential investors in making decisions.